Implementation of Game-Based Assessment Media 'SPEDU' to Measure Conceptual Understanding of Ecology and Biodiversity among 7th Grade Junior High School Students in Yogyakarta - Amalia Haq; Eka Dahliani; Laila Munazad; Nur Zamzam Yuniar Faisal; Maryati; Ismail Fikri Natadiwijaya (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This study aims to describe the effectiveness of using the game-based assessment media